(untitled) (Human Factors in Design, 2023)
This study investigated the relationship between the attrition rate of people with disabilities in distance learning courses and the usability of Moodle®. Studies in Portuguese, English and Spanish were selected from the databases Scopus, Scielo and Science Direct. Of the eight articles found, five met the selection criteria. The results indicated greater accessibility barriers for people with visual impairments compared to people with hearing impairments, and improved usability using high-quality videos and captioned tables. The study highlights the need for more research into the usability of Moodle® for people with disabilities, especially in Brazil.